Existence and Boundary Behavior of Positive Solutions of Quasi-linear Elliptic Singular Equations with a Gradient Term (Journal of Partial Differential Equations, 2020)
Existence of positive solutions of a class of quasi-linear elliptic equationwith a gradient term is obtained by using super-solution and sub-solution method. In particular, we study the asymptotic behavior of the solution near the boundary up to the second order under various assumptions on the growth of the coefficients of the equation. The results of this paper is new and extend previously known results.
Keywords: Existence; quasi-linear elliptic equation; super-solution; sub-solution